Harmonic mappings and its directional convexity - SHARMA, Poonam; Omendra MISHRA, Omendra MISHRA (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
For any $\mu _{j}\ (\mu _{j}\in \mathbb{C},\left\vert \mu _{j}\right\vert =1,j=1,2)$, we consider the rotations $f_{\mu _{1}}$ and $F_{\mu _{2}}$ of right half-plane harmonic mappings $f,F\in S_{\mathcal{H}}$ which are CHD with the prescribed dilatations $\omega _{f}(z)=\left( a-z\right) /\left( 1-az\right) $ for some $a$ $\left( -1<a<1\right) $ and $\omega _{F}(z)=$ $ e^{i\theta }z^{n}$ $\left( n\in \mathbb{N},\theta \in \mathbb{R}\right) $, $\omega _{F}(z)=$ $\left( b-z\right) /\left( 1-bz\right) $, $\omega _{F}(z)=\left( b-ze^{i\phi }\right) /\left( 1-bze^{i\phi }\right) $ $% (-1<b<1,\phi \in \mathbb{R})$, respectively. It is proved that the convolution $f_{\mu _{1}}\ast F_{\mu _{2}}\in S_{\mathcal{H}}$ and is convex in the direction of $\overline{\mu _{1}\mu _{2}}$ under certain conditions on the parameters involved. Mathematics Subject Classification (2010): 31A05, 30C45, 30C55.